DASAR FILSAFAT TEOLOGIS PLURALISME AGAMA Suatu Analisa Dan Kritik Teologi - Zebua, Rosmawati; Purwanto , Purwanto (STT Kingdom, 2025)
Philosophical basis also plays an important role in human understanding to think and provide arguments about what is in the situation where he is. However, people still philosophize and try to achieve success in sharpening their knowledge or to find out what they have been questioning in their life. But this cannot answer his criticism of the Bible or of the existence of God. Because, only God's Word is able to reach absolute understanding and truth in accepting God's existence by faith.